Resilience Capacity of Farmers in Sub-Saharan Africa: A Case Study of Rice Farmers in Ogun and Niger States, Nigeria - Agun, Williams (My University, 2022)
Food production in Sub-Saharan Africa faces challenges of which climate change is major. Being a global environmental threat of this century, the Inter-Government Panel on Climate Change estimated that if the current emissions rate of greenhouse gasses (GHGs) continues, the present warming levels are likely to reach 1.5°C between 2030 and 2052 –additional warming of 0.5°C (IPCC., 2018). This particularly is a point of concern as extreme weather events can negatively impact crop production (IPCC., 2018) . Some critical challenges that agriculture has been forecast to face under climate change are already obvious.
Keywords: Resilience Capacity; Food systems; Climate Change